The effect of Lupinus angustifolius supplementation in laying hens on the liver proteome profiles and the concentration of acute phase proteins in serum and liver - Sebastian Grabowski; Łukasz S. Jarosz; Katarzyna Michalak; Agnieszka Marek; Marcin Hejdysz; Anna Rysiak (Poultry Science, 2025)
In the search for alternative protein sources for laying hens that meet production criteria and are an alternative to soybean meal, increasing attention is being paid to the lupine seeds which have high content of proteins, essential amino acids and low content of starch and low glycaemic index. Furthermore, the effect of lupin seed supplementation to the diet of laying hens on liver protein expression and acute phase protein synthesis has not yet been determined. The aim of the study was to identify proteins synthesized in the liver of laying hens fed a diet with a high content of Lupinus angustifolius (20 % and 25 %), to determine differences in their expression, and to evaluate the concentration of acute phase proteins in serum and liver of laying hens. The obtained results indicate that supplementation of lupin at a dose of 20 % and 25 % increases the expression of proteins such as hematopoietic prostaglandin-D synthetase, SOSS complex subunit C, DNA repair protein RAD25 homolog and basic histone H1 protein in the liver, with statistically significant differences being particularly visible in the case of a dose of 25 % lupin on day 99 of the study. Moreover, the use of high doses of lupin in the diet of hens, containing various bioactive substances, caused changes in the concentration of acute phase proteins in the liver, and especially an increase in the synthesis of serum amyloid A component and haptoglobin, which may also affect the synthesis and expression of other proteins in the body, including the liver.